2007
DOI: 10.1111/j.1460-9568.2006.05258.x
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of corticofugal projections during early cortical development in a τ‐GFP‐transgenic mouse

Abstract: The first postmitotic neurons in the developing neocortex establish the preplate layer. These early-born neurons have a significant influence on the circuitry of the developing cortex. However, the exact timing and trajectory of their projections, between cortical hemispheres and intra- and extra-cortical regions, remain unresolved. Here, we describe the creation of a transgenic mouse using a 1.3 kb golli promoter element of the myelin basic protein gene to target expression of a tau-green fluorescent protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
166
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(173 citation statements)
references
References 43 publications
6
166
0
Order By: Relevance
“…Rosa-tdTomato and TetO-tdTomato mice were acquired from Jackson Laboratories (48,49). The Fezf2-GFP and Golli-tau-GFP transgenic mice are previously described (27,28). PCR genotyping was performed using published primer sets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosa-tdTomato and TetO-tdTomato mice were acquired from Jackson Laboratories (48,49). The Fezf2-GFP and Golli-tau-GFP transgenic mice are previously described (27,28). PCR genotyping was performed using published primer sets.…”
Section: Methodsmentioning
confidence: 99%
“…S4) (28), and (ii) Golli-tau-GFP mice that express a tau-GFP fusion protein under the control of the Golli gene promoter, which confers selective expression in cortical subplate and layer-6 neurons (CTAs) (Fig. S4) (27). In Fezf2-GFP;EphB1/2 DKO mice at E14.5, we observed clear L1-CAM + TCA guidance defects in the ventral VTel in a region ventral to the GFP + cortical axons (Fig.…”
Section: Ephb1 and Ephb2mentioning
confidence: 99%
“…The first nVPM-to-nRT (Mitrofanis and Baker, 1993) and corticothalamic (Jacobs et al, 2007) axons reach the nRT at birth, but there has been no systematic study of the EPSC changes with growing from P0 to P9. In the S1 cortex, previous work has shown that the relative contribution of the NMDARs at the TC synapses decreases during the first postnatal week (Crair and Malenka, 1995).…”
Section: Postnatal Development Of the Thalamic Inhibitory Feedback Loopmentioning
confidence: 99%
“…The second input originates in the layer 6 barrel cortex (L6Cx), and sends axon collaterals in the nRT before invading the nVPM (Bourassa et al, 1995;Liu et al, 2001;Ulrich, 2003, 2004). The electrical stimulation of nVPM can activate both the somatodendritic region of the nVPMto-nRT relay neurons and the axonal endings of the corticothalamic fibers that have already invaded the nVPM during the first postnatal week (Jacobs et al, 2007). Recordings were first performed during a restricted period of development (P7-P9) to investigate the possibility to discriminate nVPM-to-nRT and L6Cx-to-nRT EPSCs at Ϫ70 mV.…”
Section: Electrical Stimulation Of Nvpm Evokes Two Types Of Epsc In Nmentioning
confidence: 99%
See 1 more Smart Citation